Le LâANALYSE DE LA CONFORMITÃ DU TEST DE LA COMPREHENSION ÃCRITE POUR LA 11E ANNÃE DU 1E SEMESTRE Ã SMA NEGERI 8 SEMARANG AU STANDARD DE LA COMPÃTENCE, Ã LA COMPÃTENCE DE BASE, ET Ã LâINDICATEUR - Pratiwi, Yonnika; Widayanti, Diah Vitri; Handayani, Sri (Didacticofrancia: Journal Didactique du FLE, 2016)
SMA N 8 Semarang is one of schools using curriculum 2006 named KTSP. The teacherarranged some test to examine studentâs reading ability. A good test should be relevant withCompetence Standard, Basic Competence, and also indicator. It is descriptive-qualitative research. The aim of this research is to describe the conformity of France Language readingtest (is used in SMA N 8 Semarang) with Competence Standard, Basic Competence, andindicator. The object of this research is the item of reading test. This research used reading testquestion which is used in SMA N 8 Semarang made by French teacher in this school as thedata resource. Reading test consist of test 1, test 2, test 3,and final exam. This research useddocumentation technique to collect the data. The data were analyzed using content analysistechnique. The result shows that among 141 items of reading test, 102 points (72,34%) areconform to Competence Standard, Basic Competence and also indicator. 39 points (27,65%)were not conformed to Competence Standard, Basic Competence and also indicator